ANALYSIS OF PARTICIPATION IN PROLANIS EXERCISE PROGRAM AND ITS IMPACT ON BLOOD PRESSURE OF PATIENTS WITH HYPERTENSION - Oktarina, Mila; Hamisah, Irma; Adamy, Aulina; Arlianti, Nopa; Wardiati, Wardiati; Septiani, Riza (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2023)
Background: Hypertension remains a major public health problem globally. This disease is also one of the public health challenges in Indonesia. One of the health programs to promote health and maintaining controlled blood pressure among patients with hypertension is by optimizing the utilization of “the Chronic Disease Management Program” or “Program Pengelolaan Penyakit Kronis (Prolanis)”, and one of the interventions is exercise activities. This study aims to analyze factors associated with participation in the Prolanis exercise program and its impact on participants’ blood pressure. Method: This study uses a cross-sectional design with a sample of 106 patients with hypertension in two Community Health Centers (Puskesmas Lhoknga and Puskesmas Darul Imarah Aceh Besar). Data were collected by interview and observation of blood pressure. Data were analyzed univariate and bivariate using chi-square with significance p0.05 and unpaired t-test. Results: Chi-square analysis shows the relationship between knowledge (p-value:0.034), positive attitude (p-value 0.011), family support (p-value:0.018), self-motivation (p-value:0.022), health worker roles (p-value:0.032), and participation of Prolanis exercise program. Meanwhile, unpaired t-test analysis shows significant differences betweenmean values of blood pressure among patients with hypertension who participated and not participated in Prolanis exercise program. Recommendation: The Prolanis Exercise program has a significance impact in controlling blood pressure in hypertensive patients. It is recommended that health workers and health promotion staffs at Community Health Centers to promote and maintain the implementation of Prolanis exercise program, as well as support patients to join and actively participate in the program.